B-boys (Rio de Janeiro) and rappers (Lisbon) in search of recognition: a brief comparison - Raposo, O. (2019)
Since the first appearance of rockers, there has been an explosion of youth cultures (mods, punks, teddy boys, etc.). Today’s youth movements are now led by rappers, b-boys, funkeiros, 1surfers, goths, emos and others. Globalization has connected different countries, cultures and organizations, producing shared identities for a common, transnational community. There are now young people all over the world who rap or break-dance, enjoying aspects of so-called ‘hip-hop culture’.2This efficient means of asserting identity and gaining visibility is used by young people in the outskirts of Lisbon in Portugal, and Rio de Janeiro in Brazil, to try and counter the subordinate status thrust upon them. In this chapter, I compare the creative way in which two groups of young people –b-boys from Maré, a favela (shanty town) in Rio de Janeiro, and rappers from Arrantela, a suburb of Lisbon –appropriate cultural styles to create positive self-image and question prevailing ideas about their place in society, contributing towards new meanings for their identity as poor, young, black people. Both groups make use of performance as a way to feel their existence is valued, at the same time building more wide-reaching parameters for integration into their cities.